Analysis of Fisheries Conflict Patterns Among Traditional Fishers in Larantuka District, East Flores Regency - Nawastuti, Dati; Larantukan, Karolus Banda; Pertiwi, Widhi Netraning (ECSOFiM (Economic and Social of Fisheries and Marine Journal), 2026)
This study aimed to analyze the differences in conflict type and geographical location on fisheries conflict scores among traditional fishers in Larantuka District, East Flores Regency, using a two-way ANOVA approach. Fisheries conflicts in small-scale fisheries are commonly associated with competition over fishing grounds, unequal access to fishing technology, and pressure on marine resources. Primary data were collected through structured interviews with 45 traditional fishers from three coastal villages, with each respondent evaluating two categories of fisheries conflict, resulting in 90 observations included in the statistical analysis. The results showed that conflict scores differed significantly between the two fisheries conflict categories, indicating significant differences between the two categories of fisheries conflict evaluated in this study. Geographical location also differed significantly, suggesting that differences in local ecological, socio-economic, and institutional conditions contributed to variations in conflict scores among the study villages. However, the interaction between conflict type and geographical location was not significant, indicating that similar structural drivers of fisheries conflict exist across the study locations. These findings highlight the importance of strengthening equitable access to fisheries resources, improving community-based fisheries governance, and implementing adaptive fisheries management strategies to reduce fisheries conflicts in traditional fishing communities.